A Pine Enhanced Biochar Does Not Decrease Enteric CH4 Emissions, but Alters the Rumen Microbiota - Terry, Stephanie A.; Ribeiro, Gabriel O.; Gruninger, Robert J.; Chaves, Alex V.; Beauchemin, Karen A.; Okine, Erasmus; McAllister, Tim A. (Frontiers in Veterinary Science, 2019)
The objective of this study was to examine the effect of a pine enhanced biochar (EB) on rumen fermentation, apparent total tract digestibility, methane (CH4) emissions, and the rumen and fecal microbiome of Angus × Hereford heifers fed a barley silage-based diet. The experiment was a replicated 4 × 4 Latin square using 8 ruminally cannulated heifers (565 ± 35 kg initial BW). The basal diet contained 60% barley silage, 35% barley grain and 5% mineral supplement with EB added at 0% (control), 0.5%, 1.0%, or 2.0% (DM basis). Each period lasted 28 d, consisting of 14 d adaptation and 14 d of measurements. Samples for profiling of the microbiome in rumen liquid, solids and feces were collected on d 15 before feeding. Rumen samples for fermentation characterization were taken at 0, 3, 6, and 12 h post feeding. Total collection of urine and feces was conducted from d 18 to 22. Heifers were housed in open-circuit respiratory chambers on d 26 to 28 to estimate CH4 emissions. Ruminal pH was recorded at 1-min intervals during CH4 measurements using indwelling pH loggers. Data were analyzed with the fixed effects of dietary treatment and random effects of square, heifer within square and period. Dry matter intake was similar across treatments (P = 0.21). Ammonia N concentration and protozoa counts responded quadratically (P = 0.01) to EB in which both were decreased by EB included at 0.5 and 1.0%, compared to the control and 2.0% EB. Minimum pH was increased (P = 0.04), and variation of pH was decreased (P = 0.03) by 2.0% EB. Total tract digestibility, N balance and CH4 production were not affected (P ≥ 0.17) by EB. Enhanced biochar decreased the relative abundance of Fibrobacter (P = 0.05) and Tenericutes (P = 0.01), and increased the relative abundance of Spirochaetaes (P = 0.01), Verrucomicrobia (P = 0.02), and Elusimicrobia (P = 0.02). Results suggest that at the examined concentrations, EB was ineffective at decreasing enteric CH4 emissions, but did alter specific rumen microbiota.